Optimizing Lean Manufacturing for Timely Product Completion in Project Manufacturing Company: A Case Study - Oktavera, Rini; Yudistira, Dimas Aditya; Deviyanti, IGA Sri; Fais, Moch Ainul (International Journal of Integrated Engineering, 2025)
In this modern era, companies are eager to provide quality products and services at affordable prices and pay attention to production timelines. This study aims to implement lean manufacturing principles to overcome challenges such as delays in product completion and improve production efficiency in a company that produces tanks. Using Lean principles, Value Stream Mapping (VSM) and Value Stream Tools (VALSAT) analysis, it was found that the most common types of waste were Waiting (20%), Defective Parts (18%), and Excess Processing (15%). Process Activity Mapping (PAM) identified areas for improvement, especially in reducing transportation time (3% NNVA). This research highlights the positive impact of lean manufacturing on production efficiency and customer satisfaction. Future research projections include exploring automation technologies, integrating Industry 4.0, environmental monitoring, and employee development.